Using Microcredit to Advance Women - Khandker, Shahidur R. (World Bank, Washington, DC, 2012)
Traditional financial institutions in many countries, have often failed to provide the needy with financial services to increase their income and reduce poverty. Hence, microcredit programs have been developed to fill in this gap. This note analyzes the outreach on the poor, with particular attention on women. Specifically, it examines three microcredit programs in Bangladesh, where women participation is significant. Interestingly, these microcredit programs mobilize the needy into groups, provides training, and uses a group based lending approach, with the following attractive incentives: 1) easier credit accessibility due to personal selection of group; 2) lower loan defaults due to group pressure and monitoring upon loan enforcement; 3) availability of resources and risk diversification because of close ties across groups and communities; and, 4) savings mobilization, as an integral part of group-based lending. The note finally suggests, that even though an increase in assets may empower the needy and women, to higher consumption, thus contributing to welfare, only those with entrepreneurial ability have access to borrowing, unevenly apportioned among women and poor people, as seen in any other population group. The sustainability of these programs remains to be seen.